BRAND SOCIAL RESPONSIBILITY DAN CORPORATE SOCIAL RESPONSIBILTY DALAM RANGKA MENINGKATKAN REPUTASI DAN DAYA SAING ORGANISASI - Umu Khouroh; Fatima Abdullah (University of Merdeka Malang, 2016)
The objective of this research is to examine the effects of Brand Social Responsibility (BSR) and Corporate Social Responsibility (CSR) on the reputation and competitiveness of the organization. This methods research designedby using the explanatoryresearch.Unit analysisin this researchis students in University ofMerdeka Malang. The research instrument used questionnaires technique, collected from a sample of 150 students. Data analysis techniques used the SmartPLSanddescriptiveanalysis.This results research showed thatBrandSocial Responsibility (BSR) does not have an effect on the reputation and competitiveness. The CSR has effect on reputation but not towards competitiveness. The reputation has effect on competitiveness. CSR influences against reputational mediatedby competitiveness. Based on the research results, TheUniversity of Merdeka Malang should be continue to implementand enhancethe BSRand the CSRprogramin a moreplannedand ongoing concern as a manifestation of Business and Economics Feculty in improving knowledge, expertise and skills ofthe nation'schildren.